Nitrogen addition enhances terrestrial phosphorous retention in grassland mesocosms - Esch, Ellen; MacDougall, Andrew S. (Frontiers in Environmental Science, 2023)
Nitrogen (N) and phosphorus (P) are fundamental for plant biomass production in grasslands, are often co-limiting, and have become major freshwater pollutants. By factorially applying gradients of N and P to field-based grassland mesocosms, we tested for saturating thresholds of plant uptake as nutrients increase and whether simultaneous and potentially additive growing-season demand reduces flows of dissolved nutrients to subsurface leachate. We quantified the seasonality of nutrient losses, differences in uptake by functional group (grasses, forbs), the impacts of increasing nutrients on root:shoot ratios, and contrasted vegetated and unvegetated treatments to isolate edaphic influences. Overall, most added nutrients were retained by plants and soil - 80% for N and 99% for P. Co-limitation dynamics were powerful but asymmetrical with N additions reducing P in leachate, but P having little influence on N. N retention was primarily influenced by season – most N was lost prior to peak biomass when plant demand was presumably lower. Nutrients reduced root:shoot ratios by increasing foliage but with no detectable effect on retention, possible because root biomass remained unchanged. Similarly, there was no impact of functional group on nutrient loss. Despite substantial plant uptake, leachate concentrations of N and P still exceeded regional levels for safe drinking water and prevention of algal blooms. This work reveals how nutrient co-limitation can accelerate the capture of P by N in grasslands, indicating that plant uptake can significantly reduce dissolved subsurface nutrients. However, the offseason flows of N and the failure to meet regional water-quality standards despite capture levels as high as 99% reveal that vegetative-based solutions to nutrient capture by grasslands are important but likely insufficient without complimentary measures that reduce inputs.